The complete mitochondrial genome of Simulium jisigouense (Diptera: Simuliidae) and phylogenetic analysis of Simuliidae - An, Yuxin; Li, Cong; Li, Jing; Wang, Yuyu (Frontiers in Ecology and Evolution, 2022)
The systematic position of the family Simuliidae (Diptera) is still debated. Few mitochondrial genomes (mitogenomes) of Simuliidae and none of the subgenus Montisimulium in the genus Simulium have previously been available. Therefore, the mitogenome of Simulium jisigouense Chen, Zhang and Liu, 2008 was sequenced to better understand the diversity of mitogenomes within this family. The complete mitogenome of S. jisigouense was 16384 bp long. It contained 37 genes including 22 tRNAs, 13 protein-coding genes (PCGs), 2 rRNAs, and an A + T-rich region, which was the same as the arrangement of mitogenomes of ancestral insects. Almost all PCGs used the typical ATN as start codons, except COI used TTG. Almost all tRNAs could be folded into cloverleaf structures except the dihydorouridine (DHU) arm of tRNASer (AGN), which formed a loop. The phylogenetic analysis revealed that Simuliidae was monophyletic and was the sister group to Thaumaleidae. Subgenus Simulium was recovered as paraphyletic and needs more comprehensive sampling in future studies. Divergence time estimation showed that Simuliidae diverged from Thaumaleidae at 239.24 Ma and the subgenera of Simulium diverged from each other from 162.46 Ma to 75.08 Ma.